2023
DOI: 10.1002/admt.202301242
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ag2Se Fabricated by a Modified Cold Sintering Process with the Average zT Around Unity Near Room Temperature

Dulyawich Palaporn,
Supree Pinitsoontorn,
Ken Kurosaki
et al.

Abstract: Silver selenide (Ag2Se) is a promising material for thermoelectric applications near room temperature. This work proposes a new fabrication route for bulk Ag2Se via a modified cold sintering process (mCSP) to enhance its figure‐of‐merit (zT). Unlike conventional CSP, mCSP employs thiol‐amine (TA) as a liquid medium that completely undissolves Ag2Se, leading to a free flow of the TA solution within interparticle channels. By sintering at temperatures above the boiling point of TA, the liquid evaporates, leaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…A) total thermal conductivity, B) lattice thermal conductivity, and C) lattice thermal conductivity plotted against the microstrain obtained from XRD peak width analysis. D) Power factor, E) thermoelectric figure of merit zT , and F. average zT compared with state‐of‐the‐art literature values between 300 and 387 K. [ 45,51,69–71 ]…”
Section: Resultsmentioning
confidence: 99%
“…A) total thermal conductivity, B) lattice thermal conductivity, and C) lattice thermal conductivity plotted against the microstrain obtained from XRD peak width analysis. D) Power factor, E) thermoelectric figure of merit zT , and F. average zT compared with state‐of‐the‐art literature values between 300 and 387 K. [ 45,51,69–71 ]…”
Section: Resultsmentioning
confidence: 99%
“…As the first example, in the previous study, we have shown that the CSP-prepared PbTe 0.94 Se 0.06 has superior thermoelectric performance in comparison to spark plasma sintering prepared material owing to the low-temperature depressed Pb precipitation. Recently, thermoelectric materials such as Ca 3 Co 4 O 9 , CoSb 3 , and Ag 2 Se prepared by CSP have been reported, which show competitive performance compared with conventional sintering methods. Here, we demonstrate that in addition to the highly anisotropic structure, the high pressure of CSP can induce dislocations and stacking faults in SnSe with much higher strain compared to conventional sintering.…”
Section: Introductionmentioning
confidence: 99%